The effect of mutation status, pathological features and tumor location on prognosis ın patients with colorectal cancer - Babat,Idris (2021)
SUMMARY OBJECTIVE: Colorectal cancer is the most common malignancy of the gastrointestinal tract. It is the third most common tumor in both genders and the second reason of cancer-related deaths. In recent years, tumor location has gained importance as a prognostic indicator. In this study, we aimed to analyze if there was a prognostic effect of tumor location, the pathological features, and the mutation status of patients on survival. METHODS: Two-hundred and ten colorectal cancer patients aged 18 years and older were included into the study. One-hundred and forty-two patients had left-sided tumor and 68 patients had right-sided tumor. Patients who had other malignancies rather than squamous cell skin cancer and in situ cervical cancer were excluded. All statistical tests were carried out using two-sided process, and a p≤0.05 was considered statistically significant. RESULTS: There were 140 men and 70 women in the study. The median age of the patients was 62 years old. There was no statistically significant difference according to tumor location and survival of patients. The overall survival of patients with right-sided tumors was 60.5 months and 47.2 months for left-sided tumors. Disease-free survival of patients was 63.7 months for right-sided tumors and 46 months for left-sided ones. Perineural invasion, grade and stage were crucial prognostic parameters. Disease-free survival was longer for female colorectal cancer patients. CONCLUSION: According to our study, survival of patients was similar regardless of tumor location. This can be explained by the different sequencing of treatment strategies and divergent population genetics.